Literature Review: Political, Economic and Legal Systems in Economic Development - Bima Bryan; Tedy Syahputra Barus; Rizki Edom N. Manalu; Feronica Simanjorang (LPPM Institut Studi Islam Sunan Doe, 2024)
This study discusses the political, economic, and legal systems in Economic Development with a literature review approach. This study uses a literature review method with a descriptive approach to analyze the influence of political, economic and legal systems on economic development and their implications. The differences between collectivism and individualism, democracy and totalitarianism in political systems are the focus of discussion. Economic systems include market, command, and mixed economies. Legal systems differ and geographic and educational factors influence economic development. The broader concept of development includes social and human factors, innovation and entrepreneurship as engines of economic growth. Changes in the political economy system and geographic and educational factors have implications for economic development. This study provides insight into aspects related to the political, economic, and legal systems and their implications for economic development.